ANALYSIS OF THE EFFECTIVENESS OF TREATMENT OF BACTERIAL VAGINOSIS WITH INTRAVAGINAL DRUGS - Пилецкая, Ульяна Владимировна; Макаров, Константин Юрьевич; Соколова, Татьяна Михайловна; Дробышева, Татьяна Александровна; Хаятова, Зульфия Базарбековна; Киселева, Татьяна Вячеславовна (Mother and Baby in Kuzbass, 2022)
The aim of the study was to improve the results of treatment of women of reproductive age with bacterial vaginosis.Currently, the question of effective therapy of bacterial vaginosis remains open. A variety of treatment regimens for bacterial vaginosis pose to the clinician the question of choosing an adequate therapy for this disease. This article presents a comparative analysis of common treatment regimens for bacterial vaginosis.The study was conducted with the participation of 120 women from 18 to 45 years old living in Novosibirsk. The effectiveness of 4 treatment regimens for bacterial vaginosis with the use of drugs for vaginal administration was studied: metronidazole in gel form, clindamycin in cream form, chlorhexidine bigluconate in the form of vaginal tablets and a complex preparation containing ornidazole, neomycin, prednisolone, econazole.Based on the presented data, a conclusion is made about a more effective integrated approach to the treatment of bacterial vaginosis than with the use of schemes with the isolated use of single-component antibacterial drugs.
Keywords: bacterial vaginosis; lactobacilli; treatment regimens for bacterial vaginosis; premature birth; R. Amsel criteria